Problem-Oriented Educational Games to Improve Learning Outcomes on Flora and Fauna in Indonesia for Fifth Grade Elementary School Students - Ni Made Tiara Santika Dewi; Maria Goreti Rini Kristiantari; Komang Sujendra Diputra (Jurnal Edutech Undiksha, 2025)
The learning outcomes of fifth grade students in the subject of Social Studies are still low, this is due to the lack of student learning motivation because the teacher's learning method is still conventional. This study aims to prove the effectiveness of problem-oriented educational games on the material of flora and fauna diversity in Indonesia. This study is a development research using the ADDIE development model. The subjects of this study were 20 fifth grade students. The methods and instruments for data collection used multiple-choice tests, questionnaires, and qualitative descriptive data analysis techniques, quantitative descriptive, and inferential statistics. The results of the one-sample t-test obtained a tvalue of 4.133. The ttable value for db 19 with a significance level of 5% (α = 0.05) is 1.729. This means that tcount> ttable, so H0 is rejected and H1 is accepted. Thus, the results of this study indicate that problem-oriented educational games are effectively applied to the content of science subjects on the diversity of flora and fauna in Indonesia for grade V students. The implications of this study are that it is proven that by utilizing problem-oriented educational games on the diversity of flora and fauna in Indonesia in the learning process, there are positive changes in increasing students' interest in learning and understanding.